2018
DOI: 10.1038/s41419-017-0151-z
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin inhibits the progression of intervertebral disc degeneration through inactivation of the NF-κB pathway in rats

Abstract: Intervertebral disc degeneration (IVDD) is one of the key predisposing factors for low back pain. Although the exact mechanism remains unclear, inflammatory response and nucleus pulposus (NP) apoptosis are known to play important roles in this process. Prolactin protects against inflammation-associated chondrocyte apoptosis in arthritis. Based on prior studies, we hypothesized that prolactin might have therapeutic effects on IVDD by inhibiting the apoptosis of degenerative human disc NP cells. An experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…AF cells help to maintain the structural integrity through synthesizing and secreting normal and adequate extracellular matrix, whereas some intrinsic and extrinsic pathways activated by the detrimental pathological factors often induce AF cell apoptosis [12,13]. In the previous animal disc degeneration models [12,14], the number of apoptotic AF cells is significantly increased, indicating that AF cell apoptosis is promoted and involved in the progression of disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…AF cells help to maintain the structural integrity through synthesizing and secreting normal and adequate extracellular matrix, whereas some intrinsic and extrinsic pathways activated by the detrimental pathological factors often induce AF cell apoptosis [12,13]. In the previous animal disc degeneration models [12,14], the number of apoptotic AF cells is significantly increased, indicating that AF cell apoptosis is promoted and involved in the progression of disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…NF‐κB pathway has an essential role in IVDD pathogenesis . In the context inflammation caused by LPS, IκBα becomes phosphorylated, which triggers the translocation of p65.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB pathway has an essential role in IVDD pathogenesis. 37,38 In the context inflammation caused by LPS, IκBα becomes phosphorylated, which triggers the translocation of p65. Several researches have shown that p65 promotes transcription of inflammatory genes, for example PGE2, IL-6, COX-2, iNOS, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…In general, NP cells produce extracellular matrix (ECM) including collagen II and proteoglycans, the main components of the gelatinous tissues of NP [20]. The gelatinous NP is essential for a functional disc, and degeneration of the NP is regarded as a crucial part of IVDD [40].…”
Section: Discussionmentioning
confidence: 99%
“…9A-C). In general, gelatinous NP is the main functional composition of IVD, and degeneration of the NP is regarded as a crucial part of intervertebral disc degeneration [20]. Sham group showed the structures of NP with strong immunoreactivity for aggrecan and weak immunoreactivity for MMP-13 and ADAMTS-4.…”
Section: Composition Changes Of Np At Protein Levelmentioning
confidence: 97%